If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 3)(X + 9) = 0 Reorder the terms: (3 + X)(X + 9) = 0 Reorder the terms: (3 + X)(9 + X) = 0 Multiply (3 + X) * (9 + X) (3(9 + X) + X(9 + X)) = 0 ((9 * 3 + X * 3) + X(9 + X)) = 0 ((27 + 3X) + X(9 + X)) = 0 (27 + 3X + (9 * X + X * X)) = 0 (27 + 3X + (9X + X2)) = 0 Combine like terms: 3X + 9X = 12X (27 + 12X + X2) = 0 Solving 27 + 12X + X2 = 0 Solving for variable 'X'. Factor a trinomial. (9 + X)(3 + X) = 0Subproblem 1
Set the factor '(9 + X)' equal to zero and attempt to solve: Simplifying 9 + X = 0 Solving 9 + X = 0 Move all terms containing X to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + X = 0 + -9 Combine like terms: 9 + -9 = 0 0 + X = 0 + -9 X = 0 + -9 Combine like terms: 0 + -9 = -9 X = -9 Simplifying X = -9Subproblem 2
Set the factor '(3 + X)' equal to zero and attempt to solve: Simplifying 3 + X = 0 Solving 3 + X = 0 Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + X = 0 + -3 Combine like terms: 3 + -3 = 0 0 + X = 0 + -3 X = 0 + -3 Combine like terms: 0 + -3 = -3 X = -3 Simplifying X = -3Solution
X = {-9, -3}
| 2a/3-4-3=-2/3 | | -19p=-57 | | -(k+5)=-6k | | -222=-6x-6(x+25) | | 4x=2+8x | | 35/6+x=7 | | 6x^2-17x+13=20x^12-32 | | 9+4+x=8+5 | | 12x+10+y=180 | | 7x+3=8x+9 | | b^2+16b+64=7 | | X^2-10x+1=23 | | 2(7+6x)=34+8x | | 7x-2(5x-20)=61 | | 5-2n=12 | | -4/.5=c | | 10x-8x=30 | | 6p-12=-8+7p | | 8(7p-6)= | | 4s-8=8+8s | | (4b+3)(b-12)= | | -35=-7x+7 | | 5m^2+2=m | | 4/5y+7=47 | | 15-4x=23 | | -28/7/20=c | | 18=-36+9y | | 2.6+y=2y+8.6 | | -2(X-3)=5X-8 | | 3/5-2/3x=29 | | (6x)2= | | -5(5+2x)=-105 |